B is for balance : 12 steps toward a more balanced life at home and at work - Weinstein, Sharon (Sigma Theta Tau International, 2015)
B is for Balance is about the individual nurse -- the professional, the multi-tasker, the 'be all things to all people' leader. While the first edition of B is for Balance was well-received and has been a great resource to nurses and other professionals, the second edition has been updated to focus on 12 steps to balance, including engagement, focus, sleep deficits, fatigue, diet, re-inventing one's career, and the need for each of us to live longer and to live well. -- Provided by publisher.